The Unique Structure of Haemophilus influenzae Protein E Reveals Multiple Binding Sites for Host Factors - Singh, Birendra (American Society for Microbiology, 2013)
Haemophilus influenzae protein E (PE) is a multifunctional adhesin involved in direct interactions with lung epithelial cells and host proteins, including plasminogen and the extracellular matrix proteins vitronectin and laminin. We recently crystallized PE and successfully collected X-ray diffraction data at 1.8 Å. Here, we solved the structure of a recombinant version of PE and analyzed different functional regions. It is a dimer in solution and in the asymmetric unit of the crystals. The dimer has a structure that resembles a flattened β-barrel. It is, however, not a true β-barrel, as there are differences in both the hydrogen-bonding pattern and the shape. Each monomer consisted of a 6-stranded antiparallel β-sheet with a rigid α-helix at the C terminus tethered to the concave side of the sheet by a disulfide bridge. The laminin/plasminogen binding region (residues 41 to 68) is exposed, while the vitronectin binding region (residues 84 to 108) is partially accessible in the dimer. The dimerized PE explains the simultaneous interaction with laminin and vitronectin. In addition, we found this unique adhesin to be present in many bacterial genera of the family Pasteurellaceae and also orthologues in other, unrelated species (Enterobacter cloacae and Listeria monocytogenes). Peptides corresponding to the surface-exposed regions PE 24 to 37, PE 74 to 89, and PE 134 to 156 were immunogenic in the mouse. Importantly, these peptide-based antibodies also recognized PE at the bacterial surface. Taken together, our detailed structure of PE explains how this important virulence factor of H. influenzae simultaneously interacts with host vitronectin, laminin, or plasminogen, promoting bacterial pathogenesis.